An Analysis Of English Lesson Plan Academic Year 2012/2013 At The First Semester Of MAS Darul Ulum, Banda Aceh - Mulyani, Mulyani; Kasim, Usman (Getsempena English Education Journal, 2015)
To conduct teaching English in the classroom, a teacher requires good preparations such as lesson planning preparation. Lesson plan needs to be developed by a teacher as a direction or road map towards all activities to be done by the teacher and students in the classroom in order to achieve one or more specific competencies appropriately and effectively. There are some English teachers who still face difficulties in developing effective and systematic lesson plans for a teaching program. In fact, they tend to imitate or even copy the ones provided in the textbook and the internet. The scarcity of English teachers in having trainings and workshops related to teaching, syllabus, and lesson plan development was also the problem in this study. Furthermore, the research conducted related to or the same as this study in Indonesia is rare. Considering these problems, a study related to an analysis of English lesson plan academic year 2012/2013 at the first semester of Madrasah Aliyah Swasta (MAS) Darul Ulum, Banda Aceh was conducted. There were nine lesson plans analyzed as they were developed by the teacher for one semester.The objective of this study was to investigate whether the English lesson plans provided by the only teacher of English at the first semester of MAS Darul Ulum, Banda Aceh are appropriate with the Kurikulum Tingkat Satuan Pendidikan (KTSP) or school-based curriculum or not and to find out the difficulties encountered by the teacher of English in developing the English lesson plans in terms of non-component of lesson plan basis and component of lesson plan basis as well as the efforts made by the teacher to overcome the difficulties. For this purpose, the writer conducted a qualitative research employing four different techniques of research, namely, content analysis, questionnaire, interview, and documentary study.The qualitative data were obtained from the content analysis checklist, the questionnaire distributed to the teacher of English at the first semester of MAS Darul Ulum, Banda Aceh as well as the interview conducted to the teacher of English at the first year and the principal of MAS Darul Ulum, Banda Aceh, and also the document such as syllabus.The findings showed that the lesson plans developed by the teacher at the first semester of MAS Darul Ulum, Banda Aceh generally met the standard determined by the KTSP, Standard of Content, and Standard of Process. Specifically, all of the components of a lesson plan were covered in the lesson plans developed. However, there were deficiencies found in 6 components from most lesson plans developed by the teacher, namely, materials, methods of teaching, teaching activity, time allocation, resources, and assessments. The analysis of the questionnaire data verified by the interview data also showed that the teacher of English at the first semester of MAS Darul Ulum, Banda Aceh faced 5 difficulties related to non-component of lesson plan basis, namely, (1) lack of time because of high load of teaching, (2) lack of ability in matching between studentsâ aptitude/ability and appropriate method of teaching, (3) difficulty in developing lesson plan based on KTSP related to studentsâ individual differences, (4) difficulty in developing lesson plan based on KTSP related to studentsâ encouragement to be active learners, and (5) lack of ability in matching between technique of teaching and studentsâ learning styles. Meanwhile, the difficulties of component of lesson plan basis faced by the teacher were 4, namely, (1) difficulty in adjusting between materials of study and appropriate method, (2) difficulty in arranging the steps of teaching activity especially in pre-teaching stage, (3) difficulty in matching between methods or strategies and the competency to be achieved by the students, and (4) difficulty in matching between resources such as media or tools of learning and materials of study. Moreover, there were 4 efforts made by the teacher to overcome the problems of non-component of lesson plan basis, namely, (1) consulting to a colleague or the teacher in the similar subject of teaching, (2) learning from books, journals, and internet, (3) participating in Musyawarah Guru Mata Pelajaran (MGMP) or subject teacher discussion group, and (4) participating in seminars or workshops related to concept of teaching-learning, curriculum, syllabus and lesson plan development. Meanwhile, there were 5 efforts made by the teacher to overcome the problems of component of lesson plan basis, namely, (1) consulting to a colleague or the teacher in the similar subject of teaching, (2) learning from books, journals, and internet, (3) participating in MGMP, (4) conducting classroom action research, and (5) participating in seminars or workshops related to curriculum, syllabus and lesson plan development. It suggests that the teacher still has a few problems and deficiencies related to the teacherâs competence and pedagogic competence especially in terms of developing lesson plan. However, in terms of efforts conducted to overcome the difficulties, it suggests that the teacher is a teacher who has good personality competence.Â Key Words: Analysis, Lesson Plan, School-Based Curriculum, Standard Of Competency, Basic Competence, Indicators Of Competency Achievement